May 2022 Placement Ads (The Accounting Review, 2022)
The deadline for free position ads to be included in this section of The Accounting Review is two months prior to the desired publication in the January, March, May, July, September, or November issues. Position ads, which are free with the purchase of a job posting in the AAA Career Center, should provide all relevant information about the available positions and must include contact information or application instructions for interested candidates. For more information on how to purchase a job posting in the Career Center, or for updated, detailed information about the placement listings in this issue, please go to the AAA website at http://aaahq.org and click on “Career Center,” or call our office at 941-921-7747.THE UNIVERSITY OF OKLAHOMA, Michael F. Price College of Business, John T. Steed School of Accounting invites applications for an open rank tenured or tenure-track position starting in the 2022–2023 academic year. Applicants will be considered for appointment at the Assistant, Associate, or Full Professor rank based on achievements and experience. Endowed professorships/chairs are available for qualified candidates at the Associate or Full rank. The School's primary teaching needs are in graduate auditing. Qualified individuals may apply at: https://apply.interfolio.com/100762. Application materials should include a current vita, working paper to be presented to faculty and doctoral students, evidence of effective teaching, and names and contact information for three references. Questions regarding the search may be submitted to: Karen Hennes (khennes@ou.edu). Screening of applications will begin February 4, 2022, but applications will continue to be accepted until the position is filled.SEARCHWIDE GLOBAL seeks applications for a full-time Chief Financial Officer. The Cincinnati USA Convention & Visitors Bureau (CVB) has retained SearchWide Global to find the best candidate to serve as the principal financial advisor and strategic partner to their CEO. This is a high-profile and important leadership position; the CFO represents the Cincinnati USA CVB with business leaders, community organizations, government leaders, and other thought leaders to fulfill the organization's strategic initiatives. If interested in learning more about this great opportunity, please send your resume to: info@searchwideglobal.com. Be sure to mention this ad and the position. If you are interested in learning more about other opportunities, visit https://searchwideglobal.com/THE AMERICAN ACADEMY OF PEDIATRICS (AAP), the nation's leading advocacy organization for children's healthcare, is seeking candidates for Manager, Accounting. Candidates must have strong payroll management experience, preferably with ADP. This position will manage payroll and general accounting functions, state sales tax, and year-end audit support, as well as assist with managing tax returns, month-end close, and major account reconciliations. Reporting to the Senior Manager, Finance and Accounting at our Chicago suburb headquarters in Itasca, IL, this role will work remotely until at least March 25, 2022, with a hybrid re-entry plan. All AAP employees must be fully vaccinated against COVID-19. Requirements: Bachelor's degree in accounting and 4+ years' related accounting experience required, including payroll, tax filings, fiscal year-end processing and general ledger. CPA preferred. To learn more about the organization, see a full job description, and/or apply for the position, please visit: https://www.aap.org/employmentBINGHAMTON UNIVERSITY, SUNY, School of Management invites applications for a tenure-track position at the Assistant Professor level in Accounting starting mid-August 2022. Candidates must have an earned Ph.D. degree by the time of appointment and demonstrate the ability to conduct high-quality research as evidenced by publication in the top-tier accounting journals as well as high-quality teaching in the classroom. The teaching component (2 + 2) requires delivering required/elective courses in Accounting at the undergraduate, master's and/or doctoral levels. Service and interaction with the professional community commensurate with the rank of assistant professor are expected. The qualified candidate will also contribute to the intellectual environment of the area. Application materials must be submitted electronically for consideration. Interested candidates should post a curriculum vita and other supporting documents to the appropriate position listing at: https://binghamton.interviewexchange.com/BNU-HKBU UNITED INTERNATIONAL COLLEGE (UIC), located in Zhuhai, PRC and founded jointly by Beijing Normal University and Hong Kong Baptist University, is taking the lead in implementing liberal arts education in China. The Division of Business and Management is now inviting established researchers or scholars of international stature who can take on the role of intellectual leadership and contribute to the development of the Division's research strategy. Candidates with a background in Accounting, Economics, Finance, Management of Human Resources, Marketing Management, e-Business Management & Information Systems, or Entrepreneurship & Innovation are welcome to apply. A competitive remuneration package includes annual leave, housing allowance or arrangement, medical benefits, a generous start-up fund, and relocation allowance. If you are interested in this position, please send your curriculum vitae by email to: recruit@uic.edu.cn. For more information about UIC, please visit:TAR https://uic.edu.cn/en/